Carbon stock assessment of Rani community forest in Makawanpur district and its role in climate change mitigation - Ghimire, Pramod; Lamichhane, Uchita (Journal of Agriculture and Natural Resources, 2025)
Accurately measuring forest carbon (C) stocks is crucial for evaluating Community Forests' contribution to mitigating climate change and for bolstering Nepal's carbon-based payment systems. In order to determine the importance of Rani Community Forest in Makawanpur District for mitigating climate change, this August 2024 study evaluated the forest's capacity to store carbon. In accordance with the MoFSC Guideline for Forest Carbon Measurement (2010), 31 concentric circular plots were sampled. Aboveground and belowground biomass carbon stocks were estimated following national guideline-recommended allometric equations, and Soil organic carbon (0–30 cm) was analyzed using the Walkley–Black method (1934). Results showed that total vegetation biomass was 292.21 t ha⁻¹, corresponding to total vegetation carbon stock 137.33 t ha⁻¹ where trees/poles contributed 91.98% of vegetation carbon. As a result, the total SOC stock was 79.73 tha⁻¹, with an average soil bulk density of 1.23 g cm⁻³ and a SOC content of 2.17%. The maximum SOC was found in the 0–10 cm layer, and a one-way ANOVA showed significant variations in SOC throughout depths (p <0.004). A significant positive correlation (r = 0.62, p < 0.001) between SOC and aboveground vegetation carbon indicated strong vegetation–soil linkages. The total carbon stock of 217.05 t ha⁻¹ corresponds to 796.57 t ha⁻¹ Carbon-dioxide (CO2,) demonstrating substantial carbon sequestration potential. These findings emphasize the critical role of Community Forests in Nepal's climate mitigation strategies and their potential contribution in REDD⁺ and carbon financing mechanisms.